2000
DOI: 10.1046/j.1365-2664.2000.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Moth assemblages as indicators of environmental quality in remnants of upland Australian rain forest

Abstract: Summary1. Despite great concern about the eects of fragmentation on biodiversity, quantitative studies are still scarce with respect to many major groups and important environments. Well-studied natural reference sites are few. 2. Extensive light trapping surveys for moths were thus carried out in both dry and wet seasons in nine remnants of complex notophyll vine forest on basalt on the Atherton Tablelands in tropical north Queensland, Australia. Three sites had never been cleared, three secondary sites had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
156
1
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(172 citation statements)
references
References 40 publications
(37 reference statements)
2
156
1
13
Order By: Relevance
“…Os lepidópteros, uma das principais ordens de insetos quanto à riqueza de espécies, são adequadas para estudos sobre a biodiversidade (Intachat & Woiwod, 1999;Landau et al, 1999;Kitching et al, 2000;Hawes et al, 2009). Os arctiídeos estão entre as principais famílias de lepidópteros noturnos utilizados em monitoramento de ecossistemas naturais (Hilty & Merenlender, 2000;Freitas et al, 2006) e alguns estudos mais recentes vêm ressaltando esta importância (Hilt & Fiedler, 2005;2006;Brehm & Axmacher, 2006;Brehm, 2007;Hilt, et al, 2007;Conner, 2009;Hawes et al, 2009).…”
Section: Introductionunclassified
“…Os lepidópteros, uma das principais ordens de insetos quanto à riqueza de espécies, são adequadas para estudos sobre a biodiversidade (Intachat & Woiwod, 1999;Landau et al, 1999;Kitching et al, 2000;Hawes et al, 2009). Os arctiídeos estão entre as principais famílias de lepidópteros noturnos utilizados em monitoramento de ecossistemas naturais (Hilty & Merenlender, 2000;Freitas et al, 2006) e alguns estudos mais recentes vêm ressaltando esta importância (Hilt & Fiedler, 2005;2006;Brehm & Axmacher, 2006;Brehm, 2007;Hilt, et al, 2007;Conner, 2009;Hawes et al, 2009).…”
Section: Introductionunclassified
“…Most of these studies found that both elevation and plant species distributions are important predictors of moth family distributions and diversity patterns. In temperate regions, studies addressing community structure and diversity of nocturnal macromoths have mostly been undertaken in relatively flat topography and/or homogenous vegetation types (e.g., grassland, deciduous forest, riparian forest) (Usher and Keiller 1998, Kitching et al 2000, Summerville and Crist 2003, Ober and Hayes 2010, Summerville 2011. Less is known about how nocturnal macromoth community structure and diversity respond to steep vegetational and elevational gradients at the landscape scale in temperate regions.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their dependence on host-plants, the abundance and distribution of macromoth species may reflect vegetation distribution patterns as well as plant phenology (Novotny et al 2005(Novotny et al , 2006, although some studies found that plant diversity did not predict macromoth diversity , Axmacher et al 2004, Beck and Chey 2007. Nocturnal macromoth species distribution and diversity have been related to the presence of rare habitats , vegetation disturbance (Holloway 1985, Kitching et al 2000, Kuussaari et al 2007, land use and habitat shifts (Erhardt and Thomas 1991, Ricketts et al 2001, Baur et al 2006, habitat size and distribution (Usher and Keiller 1998, Ober and Hayes 2010, and topographic influences on temperature and predation , Beck and Chey 2008, Axmacher et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I diversi tipi forestali esaminati in questo studio sono caratterizzati da comunità di Lepidotteri peculiari, il cui studio completo offrirebbe numerose chiavi interpretative delle complesse interazioni ecologiche. Ciononostante, è possibile individuare alcune caratteristiche della struttura nelle biocenosi che possono dare indicazioni abbastanza attendibili sulla naturalità degli ecosistemi e che prescindono dalla specie arborea dominante (Kitching et al 2000). Di fatto, i risultati ottenuti in questo studio mostrano una stretta rispondenza tra la struttura delle comunità di Lepidotteri e le caratteristiche dei popolamenti forestali.…”
unclassified